2021
DOI: 10.1007/s00347-021-01527-w
|View full text |Cite
|
Sign up to set email alerts
|

iOCT in der klinischen Anwendung

Abstract: Zusammenfassung Hintergrund Die Beurteilung der intraoperativen Veränderung der Netzhautmorphologie, insbesondere des vitreoretinalen Überganges, ist mithilfe der intraoperativen optischen Kohärenztomografie (iOCT) möglich geworden. Ziel der Arbeit Um die Bedeutung der intraoperativen Morphologie beim durchgreifenden Makulaforamen (MF) für das postoperative funktionelle Ergebnis zu evaluieren, wurde eine retrospektive, klinische Beobachtungss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Previous studies focused on iOCT as an additional intraoperative diagnostic tool, that can aid therapeutic decision-making during surgery and influence the further surgical strategy, e.g. in patients with vitreous haemorrhage, full thickness macular holes, ERM, submacular haemorrhage and vitreomacular surgery in highly myopic eyes [16][17][18][19][20][21][22][23][24] . It was concluded that iOCT, as it offers immediate visualization of retinal anatomy and instrument-tissue-interactions during peeling, adds to the understanding of intraoperative traumatic changes due to the peeling procedure [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies focused on iOCT as an additional intraoperative diagnostic tool, that can aid therapeutic decision-making during surgery and influence the further surgical strategy, e.g. in patients with vitreous haemorrhage, full thickness macular holes, ERM, submacular haemorrhage and vitreomacular surgery in highly myopic eyes [16][17][18][19][20][21][22][23][24] . It was concluded that iOCT, as it offers immediate visualization of retinal anatomy and instrument-tissue-interactions during peeling, adds to the understanding of intraoperative traumatic changes due to the peeling procedure [10] .…”
Section: Discussionmentioning
confidence: 99%